2021
DOI: 10.1093/sleep/zsab096
|View full text |Cite
|
Sign up to set email alerts
|

Different circadian rest–active rhythms in Kleine-Levin syndrome: a prospective and case–control study

Abstract: Study objectives Kleine-Levin-syndrome (KLS) is a rare recurrent hypersomnia. Our study aimed at monitoring the movements of patients with KLS using actigraphy and evaluating their circadian rhythm. Methods Twenty young patients with KLS and 14 age-matched controls were recruited. Each individual wore an actigraphy for more than 6 months to monitor at least two attacks. Controls kept wearing the device for at least 7 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Even though actigraphic recordings are usually several days long, the fluctuation functions of activity signals in the relevant studies are generally evaluated over timescales ranging only from a few minutes to some hours 29 , 47 49 , while activity signals recorded during sleep 33 , 34 , 50 and wakefulness 51 , 52 are typically analysed separately. Although these DFA-based studies identified power-law scaling, they were typically limited to a given activity type and to assess how different diseases (i.e., Alzheimer’s disease 51 , Klein-Levin disease 47 , depression 53 , bipolar disorder 54 , autism spectrum disorder 34 ) or even aging 55 break down the patterns compared to control groups without giving a detailed description of the general fluctuation patterns of human activity. Regarding frequency-domain analysis, some studies 6 , 56 , 57 have already noted in the case of two given types of activity signals (up to 1-week-long time series, examined over their entire length) that they contain 1/ f fluctuations above the frequency of the daily rhythmicity without giving further details on the general spectral characteristic.…”
Section: Analysis Of Human Activity Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though actigraphic recordings are usually several days long, the fluctuation functions of activity signals in the relevant studies are generally evaluated over timescales ranging only from a few minutes to some hours 29 , 47 49 , while activity signals recorded during sleep 33 , 34 , 50 and wakefulness 51 , 52 are typically analysed separately. Although these DFA-based studies identified power-law scaling, they were typically limited to a given activity type and to assess how different diseases (i.e., Alzheimer’s disease 51 , Klein-Levin disease 47 , depression 53 , bipolar disorder 54 , autism spectrum disorder 34 ) or even aging 55 break down the patterns compared to control groups without giving a detailed description of the general fluctuation patterns of human activity. Regarding frequency-domain analysis, some studies 6 , 56 , 57 have already noted in the case of two given types of activity signals (up to 1-week-long time series, examined over their entire length) that they contain 1/ f fluctuations above the frequency of the daily rhythmicity without giving further details on the general spectral characteristic.…”
Section: Analysis Of Human Activity Patternsmentioning
confidence: 99%
“…In conclusion, previous studies have already partially examined the scale-free nature of human activity by analysing fluctuation functions of activity signals for box widths of less than 24 h typically separating into sleep and wakefulness for medical purposes 29 , 33 , 34 , 47 52 , PSDs of two given types of several-day-long activity signals over the entire frequency range 6 , 56 , 57 , and fluctuations of acceleration signals both with DFA and PSD (using Welch’s method) over a narrower timescale and frequency range, respectively 46 . …”
Section: Analysis Of Human Activity Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed actigraphic sleep measures have good discriminant capabilities in assessing narcolepsy type 1 nychthemeral disruption in drug-naïve children and indicated the sensibility of actigraphic assessment in the diagnostic work-up of childhood narcolepsy type 1 [ 44 ]. Actigraphy also offers the possibility to longitudinally follow up children and has the potential to become a key tool for tailoring treatment in pediatric patients [ 45 , 46 ]. Two standard sleep study tests are traditionally performed.…”
Section: Evaluation and Diagnosis Of Pediatric Narcolepsymentioning
confidence: 99%
“…They used the actigraphy to record the sleep and wake profile objectively after 1 year sodium oxybate treatment. Their results showed that symptoms severity of narcolepsy and children's anthropometric features were changed and improved as expected [45]. Although the mechanism of action of sodium oxybate is not fully understood, therapeutic effects on EDS are hypothesized to be mediated through modulation of GABA-B receptors during sleep [70].…”
mentioning
confidence: 99%